Architects and Librarians under Pressure: Dialoguing about Renovation of a Library in a Constrained Environment - Lohisse, André; Sogno, Françoise (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
A librarian and an architect conduct the essential dialogue involved in renovating an academic library in Paris, comparing architectural concerns with the exigencies of public use, and juxtaposing technical requirements with the functional organisation of the library.